The Influence of Training and Mentoring on Employee Performance through Competence at the Class B Search and Rescue Office in Jambi - Iyusnawati, Iyusnawati; Bukit, Pantun; Hapsara, Osrita (Journal of Accounting and Finance Management, 2024)
The Jambi Class B Search and Rescue Office is a government agency in the province of Jambi, Indonesia, which has the main task of carrying out search and rescue operations in emergency situations, such as searching for missing drowned people, shipwrecks, or natural disasters. This research aims to find out and describe the picture of training, mentoring, competency and performance of employees at the Jambi Class B Search and Rescue Office and to find out and analyze the influence of training and mentoring on employee performance through competency at the Jambi Class B Search and Rescue Office. The method used in this research is descriptive verification and quantitative methods. The research objects in this study were employees at the Jambi Class B Search and Rescue Office. Based on the approach, it can be seen that the number of samples is 65 people. This research uses the path analysis method. Based on the description of training in the good category, mentoring in the right category, competency in the high category and performance in the high category. Based on the research results, training and mentoring simultaneously have a significant effect on competency. Furthermore, training and mentoring partially have a significant effect on competency. Training and Mentoring simultaneously have a significant effect on Performance. Furthermore, partial training has no significant effect on performance and partial mentoring has a significant effect on performance. Competency partially has a significant effect on employee performance at the Jambi Class B Search and Relief Office.